Karakteristik Penilaian Pembelajaran Pada Kurikulum 2013 Di MI - Hafidhoh, Noor; Rifa’i, Muhammad Rizal (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2021)
Assessment has a big role in determining educational success. A good assessment has an impact on the learning process and becomes a reference for further policies. The accuracy of the selection of the assessment method will greatly affect the objectivity and validity of the results of the assessment, which ends up being objective and valid information on the quality of education. Assessment of learning outcomes by educational units aims to assess the achievement of Graduate Competency Standards for all subjects by considering the results of student assessments by educators. The assessment of learning outcomes in the 2013 Curriculum is carried out by educators and educational units through the stages of reviewing the syllabus as a reference for assessment planning, making instrument grids and determining assessment criteria, implementing assessments in the learning process, analyzing assessment results and providing follow-up on assessments carried out by students. educators, compile reports on the results of the assessment in the form of a description of the achievement of competencies and a description of attitudes. Given the importance of implementing a good assessment in supporting the implementation of the curriculum, it is necessary to have a study on how to implement the assessment in the 2013 Curriculum